Interpretation of building regulations by local authorities / Yusmarina Maslin Ya'acob - Maslin Ya'acob, Yusmarina (2006)
Interpretation of building regulations by local authorities will raise an impact on submission of building plans for approval. Local authorities in Building Control Department or Building Department are responsible on submission of building plans for approval. The role of these departments to control all types' construction such as approval for new proposed building. Local authorities enforce the Uniform Building by Laws 1984 but they also have their own building guidelines for approval of building plan submissions. Although they enforce Uniform Building by-Laws, the local authorities still follow their own guidelines. The intention of this study is to investigate the impact of interpretation of building regulations by local authority on the submission of building plans for approval. The research identifies the different building regulations by each of local authorities in Klang Valley. Before constructing a building, the client should submit the plan to the local authority to ensure that they fulfill the entire requirement needed to comply with the regulations. This research involves a qualitative methodology. The qualitative study was to examine the respondent of the local authority in Klang Valley area. 50 questionnaire were distributed and 50 respondents returned the questionnaire for analysis of the interpretation of building regulations by local authority.